"Listen to Them and Give Them a King": Self-Determination, Democracy, and the Proportionality Principle. Issue 2 (3rd August 2018) - Campagna, Giordana; Fasel, Raffael N.
Abstract : Is a right to democracy compatible with the right to self-determination? According to some, the two rights are incompatible because a right to democracy would prevent a people from choosing not to live in a democracy. As a result, these Incompatibilists argue, there can be no right to democracy. We argue that the Incompatibilists are right in that the two rights can indeed conflict. They are wrong, however, in that such conflicts do not preclude the mutual existence of both rights. To show why, we distinguish between two elements of self-determination and argue that the right to self-determination and the right to democracy each protect a different element. Arguing that both rights are best understood as principles that can be balanced using the proportionality principle, we reveal how, depending on the concrete circumstances, one right can outweigh the other without ceasing to exist, and thereby prove the Incompatibilists wrong.